Applying NAEP to Improve Mathematics Content and Methods Courses for Preservice Elementary and Middle School Teachers. (December 2014) - Goodson‐Espy, Tracy; Cifarelli, Victor V.; Pugalee, David; Lynch‐Davis, Kathleen; Morge, Shelby; Salinas, Tracie
<x xml:space="preserve">Abstract</x> This study explored how mathematics content and methods courses for preservice elementary and middle school teachers could be improved through the integration of a set of instructional materials based on the National Assessment of Educational Progress (NAEP). A set of eight instructional modules was developed and tested. The study involved 7 university instructors and 542 preservice teachers (PSTs) from three different universities. A quasi‐experimental nonequivalent groups design was used for this study in which the following data sources were collected and analyzed. Three versions of a Learning Mathematics for Teaching test were given to assess PSTs' mathematical content knowledge for teaching: (a) Elementary Number Concepts and Operations—Content Knowledge; (b) Elementary Geometry—Content Knowledge; and (c) Middle School Number Concepts and Operations—Content Knowledge. In addition, the Mathematics Teacher Efficacy Beliefs Instrument was given to assess PSTs' teacher efficacy beliefs. Test results were analyzed using paired samples t‐tests. Findings suggest that use of instructional materials, based on NAEP, with PSTs results in increases in their mathematical content knowledge for teaching and in their teaching efficacy beliefs.